On-Grid Photovoltaic (PV) - Battery - PLN for Smart Home System - Abdurrahman, Tanridio Silviati Delfina; Basalamah, Abdullah; Salmiah, Salmiah; Rahman, Muhammad Natsir (Program Studi Teknik Elektro Universitas Khairun, 2024)
Electricity is one of basic human needs. However, PLN's ability to meet customer demands is hampered by its limitations. On the other hand, the sunny geographical advantage of Makassar city can be utilized as a new renewable and environmentally friendly energy source in a smart home. Smart house is a family residence that is able to synergize electricity usage based on the habits of its residents with the help of smart technology so that comfort, safety and efficiency of using electrical energy are obtained. The utilization of solar cell hybrid power – battery – PLN can be implemented in addition to meeting the needs of electricity load in the smart home, it can also contribute excess energy to fulfill off-grid building load. Monte Carlo Simulation (MCS) is carried out at the beginning of data processing by randomly generating 24-hour models of solar irradiance and smart home load requirements along with weather conditions. PLN not only takes over fulfilling the needs of the smart home load when there is less and or no sunlight and minimum battery capacity conditions, but also it will charge the battery capacity up to 100% every midnight. On average, the daily load requirement for a smart home is almost half the energy produced by PVs, which are 12,439 kW and 24,509 kW respectively. Furthermore, the smart home hybrid power is capable of producing 8,946 MW of excess energy in a year to serve the off-grid building load needs.